2021
DOI: 10.3390/s21072288
|View full text |Cite
|
Sign up to set email alerts
|

Can Machine Learning with IMUs Be Used to Detect Different Throws and Estimate Ball Velocity in Team Handball?

Abstract: Injuries in handball are common due to the repetitive demands of overhead throws at high velocities. Monitoring workload is crucial for understanding these demands and improving injury-prevention strategies. However, in handball, it is challenging to monitor throwing workload due to the difficulty of counting the number, intensity, and type of throws during training and competition. The aim of this study was to investigate if an inertial measurement unit (IMU) and machine learning (ML) techniques could be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…14 The application of such psychological strategies is crucial for the athletes, as it promotes better coping skills during competitions. 8,9 The utilization of machine learning has gained popularity due to attention in recent years within the sporting domain, particularly in activity recognition, [15][16][17] match outcome predictions [18][19][20] and performance analysis 9,21,22 amongst others. For instance, van den Tillaar et al 23 evaluated the classification of different handball throws, apart from the prediction of ball velocity, through the employment of different supervised machine learning models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The application of such psychological strategies is crucial for the athletes, as it promotes better coping skills during competitions. 8,9 The utilization of machine learning has gained popularity due to attention in recent years within the sporting domain, particularly in activity recognition, [15][16][17] match outcome predictions [18][19][20] and performance analysis 9,21,22 amongst others. For instance, van den Tillaar et al 23 evaluated the classification of different handball throws, apart from the prediction of ball velocity, through the employment of different supervised machine learning models.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of machine learning has gained popularity due to attention in recent years within the sporting domain, particularly in activity recognition, 1517 match outcome predictions 18–20 and performance analysis 9,21,22 amongst others. For instance, van den Tillaar et al 23 evaluated the classification of different handball throws, apart from the prediction of ball velocity, through the employment of different supervised machine learning models. A classification accuracy (CA) between 79% and 87% was reported to be attained via the Gradient Boosting Machine, while an excellent prediction of the ball speed was obtained through a variation of the Support Vector Machine (SVM) model.…”
Section: Introductionmentioning
confidence: 99%
“…In tennis, IMU and various machine learning techniques demonstrated high accuracy in classifying shot count and type during training sessions (17). In handball, van den Tillaar et al (18) investigated the use of IMU and machine learning techniques to classify different throw types and to estimate peak ball velocity under controlled conditions. They reported that throw type could be predicted with between 80% and 87% accuracy.…”
mentioning
confidence: 99%